Introducing the biogeographic species pool - Carstensen, Daniel Wisbech; Lessard, Jean-Philippe; Holt, Ben G.; Krabbe Borregaard, Michael; Rahbek, Carsten (Wiley, 2013)
The species pool concept has played a central role in the development of ecological theory for at least 60 yr. Surprisingly, there is little consensus as to how one should define the species pool, and consequently, no systematic approach exists. Because the definition of the species pool is essential to infer the processes that shape ecological communities, there is a strong incentive to develop an ecologically realistic definition of the species pool based on repeatable and transparent analytical approaches. Recently, several methodological tools have become available to summarize repeated patterns in the geographic distribution of species, phylogenetic clades and taxonomically broad lineages. Here, we present three analytical approaches that can be used to define what we term 'the biogeographic species pool': distance-based clustering analysis, network modularity analysis, and assemblage dispersion fields. The biogeographic species pool defines the pool of potential community members in a broad sense and represents a first step towards a standardized definition of the species pool for the purpose of comparative ecological, evolutionary and biogeographic studies. © 2013 The Authors.